Environmental Policy and Heterogeneous Labor Market Effects: Evidence from Europe - Matthias Niggli; Christian Rutzer (University of Basel, Center of Business and Economics (WWZ), 2020)
In this paper, we use a data-driven approach to predict the "green potential" of ISCO occupations based on their corresponding skills. With this information, we can investigate the relationship between environmental regulations and occupation-level employment in the manufacturing sector of 19 European countries for the period 1992-2010. Our empirical results highlight heterogeneous occupational employment changes in response to an increase in environmental policy stringency. More specically, we nd a decrease in labor demand for occupations with relatively low green potential and an increase for occupations with relatively high green potential. Thus, at least in the short term, greening the economy may create winners and losers across occupations and countries.
Keywords: J23; J24; Q52; 330; environmental regulation; green transition; labor market; supervised learning